ETHNIC MODELS OF IDENTITY FORMATION IN CHILDREN AGED 5 TO 18 YEARS - Nakova-Manolova, Albena Ilieva; Milenkova, Valentina Georgieva; Chengelova, Emilia Evgenieva (Psychological thought, 2025)
The article examines the formation of national and ethnic identity in the process of ontogenesis in children from 5 to 18 years of age from the three main ethnic communities in Bulgaria - Bulgarians, Turks and Roma. Models of national and ethnic identity formation specific to children from each of the three ethnic groups are derived based on tracing children's sequential formation of certain notions/indicators (cognitive and affective/еmotional) of national and ethnic identity. In the study of the successive changes in the formation of the notion of national and ethnic identity in the process of ontogenesis, as a theoretical basis was used the concept of the great Swiss psychologist Jean Piaget on the stages of intellectual development. The data in the article are based on two comprehensive case studies conducted in kindergarten and secondary school (with all children attending the kindergarten and the school aged 5 to 18) in a small town with an ethnically mixed population in Bulgaria, where for centuries representatives of the three ethnic communities studied - Bulgarians, Turks and Roma - have lived in close coexistence, which is why the patterns of ethnic and national identity formation derived can be seen as typical for the town.